A new perspective of the structural complexity of HCMV-specific T-cell responses (Revision 1). - Sylwester, A; Nambiar, K; Caserta, S; Klenerman, P; Picker, L; Kern, F (Elsevier, 2016)
In studies exploring the effects of HCMV infection on immune system ageing ('immunosenescence'), after organ transplantation or in other settings, HCMV-specific T-cell responses are often assessed with respect to purportedly 'immunodominant' protein subunits. However, the response structure in terms of recognized antigens and response hierarchies (architecture) is not well understood and actual correlates of immune protection are not known.We explored the distribution of T-cell response sizes and dominance hierarchies as well as response breadth in 33HCMV responders with respect to>200HCMV proteins.At the individual responder level HCMV-specific T-cell responses were generally arranged in clear dominance hierarchies; interestingly, the number of proteins recognized by an individual correlated closely with the size of their biggest response. Target-specificity varied considerably between donors and across hierarchy levels with the presence, size, and hierarchy position of responses to purportedly 'immunodominant' targets being unpredictable.Predicting protective immunity based on isolated HCMV subunit-specific T-cell response is questionable in light of the complex architecture of this response. Our findings have important implications for T-cell monitoring, intervention strategies, as well as the application animal models to the understanding of human infection.